Analisis Kemampuan Pemecahan Masalah Matematis Siswa Fase C SDN 161 Sukapura: indonesia - Perdana, Aditya; Neneng Tita Rosita (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2025)
Mathematical problem-solving skills are needed in the development of21st century skills. This assessment aims to analyze the mathematical problem-solving skillsof students in phase C at Negeri 161 Sukapura, Bandung City. This researchuses a qualitative method with a descriptive approach. The populationof this study is a sample of 27 students in class 6C in one learning group. Data collection was carried out by administering a test consisting of two essay questions covering indicators of mathematical problem-solving skills, namely: understanding problems, planning strategies,implementing plans, and rechecking. Based on the results of the research test, the average score was 15.908 with a maximum score of 60.00 and aminimum score of 10.00. The distribution of problem-solving abilitiesranged from very low to adequate. Five students, or 18.51%, were classified as adequate, seven students, or 25.92%, were classified as low, and 15 students, or 55.55%, were classified as very low55.55%. Meanwhile, the analysis of Polya's stages showed thatunderstanding the problem was 35.80%, planning the problem was 39.81%, implementingthe plan was 19.13%, and reflecting was 9.25%.The results of the stages indicate that the stages of implementing the plan and reflectionhave the lowest percentages. Based onthe results of the study, the level of achievement of students' abilities in general is still verylow and has not reached the expected competency standards.